Exposure to Transnational Maritime Crime in the Pacific Islands Region - Jade Lindley; Sarah Lothian (Ocean and Society)
Although the Pacific Islands are strategically located alongside important trade routes, between the Global North and Global South countries and among plentiful fishing grounds, this region is considered among the lowest risk for land‐based organized crime. Grouped as a uniform region, collectively, the Pacific islands are anything but. The region consists of three ethnogeographic subregions with varying colonial, cultural, and legal legacies. Geographically, the Pacific Island states are remote, with small populations dispersed across many islands, some of which are uninhabited, limiting the ability to adequately surveil and protect this extensive maritime domain, creating porous land and sea borders. These challenges increase the complexity of policing the large exclusive economic zones of the region and therefore increase its vulnerability and potential exposure to various transnational organized crimes on land and at sea. Drawing on Kelling and Wilson’s broken windows theory, this article considers from a theoretical perspective, how international law can be used as a framework to guide Pacific Island states in achieving strengthened, region‐led resilience to transnational maritime crime in the pursuit of maritime justice.